Complementizers kad and jog(ei) ‘that’ in the 19th century Lithuanian fiction texts - Jasionytė-Mikučionienė, Erika (Lietuvių kalba, 2025)
The paper examines the functions of the complementizers kad and jog(ei) ‘that’ in the 19th-century Lithuanian fiction texts. In Lithuanian grammars, the examined complementizers are described as asemantic, i. e., conjunctions without a defined meaning (see LKG III 1976; DLKG 2006). More recent studies of the contemporary Lithuanian language (Holvoet 2010, 2015; Jasionytė-Mikučionienė 2018) confirm this conclusion: the complementizers kad and jog are associated with both complement and adverbial sentence linking strategies. However, a more detailed analysis of the complementizers at earlier stages of language development as well as an explanation of their functional differences are still lacking. Thus, the aim of this paper is to investigate the functions and syntactic environment of the complementizers kad and jog(ei) in the 19th-century Lithuanian fiction texts. The data was retrieved from a newly compiled 19th-century text corpus, which includes works of fiction by the most prominent Lithuanian writers who lived and worked in the 19th century.
Keywords: complement; complement clause; complementizer; adverbial clause; adverbial conjunction